2012
DOI: 10.1371/journal.pone.0041014
|View full text |Cite
|
Sign up to set email alerts
|

Smoking during Pregnancy Is Associated with a Decreased Incidence of Obstetric Anal Sphincter Injuries in Nulliparous Women

Abstract: BackgroundSmoking is a modifiable lifestyle factor that has been shown to be associated with adverse perinatal outcomes and to have adverse health and dose-dependent connective tissue effects. The objective of this study was to examine whether smoking during pregnancy was associated with the incidence of obstetric anal sphincter injuries (OASIS) among six birthweight groups in singleton vaginal deliveries, considering nulliparous and multiparous women separately between 1997 and 2007 in Finland.MethodologyA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Additionally, we reported a 40% reduction in the occurrence of OASIS among women who smoked until the end of their pregnancy; however, the results were not significant when we adjusted for a number of variables, including birthweight. Our results were in line with a recent study from Finland that showed nulliparous women who smoked during pregnancy had a 28% lower incidence of OASIS than non‐smokers, but this association was observed regardless of birthweight . It is well established that women who smoke deliver smaller infants, and this may explain why smoking protects against OASIS .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, we reported a 40% reduction in the occurrence of OASIS among women who smoked until the end of their pregnancy; however, the results were not significant when we adjusted for a number of variables, including birthweight. Our results were in line with a recent study from Finland that showed nulliparous women who smoked during pregnancy had a 28% lower incidence of OASIS than non‐smokers, but this association was observed regardless of birthweight . It is well established that women who smoke deliver smaller infants, and this may explain why smoking protects against OASIS .…”
Section: Discussionsupporting
confidence: 92%
“…A weakness was that the lack of data precluded adjusting for factors like maternal smoking, delivery position, body mass index (BMI) and duration of second stage, which have been associated with OASIS and may have confounding effects on the occurrence of OASIS. 6,10,[15][16][17] We have previously reported a time trend in OASIS, 6 resulting in increasing occurrence from 1967 to 2004. Possible explanations for the increase of OASIS in this period include: (1) improved routines for the registration of OASIS in the medical birth registry; (2) improved diagnostic attention and routines; (3) a change of classification during this time period; and (4) changes in obstetric and demographic risk factors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The demographic and obstetric risk factors for OASIS are well-established, including first vaginal birth [2], [3], high birthweight [4], [5], prolonged active second stage of birth [3], vacuum and forceps deliveries [2], [5], and midline episiotomy [6][8]. We previously reported that smoking during pregnancy was associated with a decreased risk of OASIS, even after adjustment for birthweight [9]. In contrast to this negative association with OASIS, smoking has typically been identified as a risk factor for pelvic floor disorders in later life, including moderate associations with a variety of bladder storage symptoms [10], urinary incontinence (UI) [11], and faecal incontinence [12].…”
Section: Introductionmentioning
confidence: 99%